2016
DOI: 10.1186/s12933-016-0330-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 predicts inflammation-induced increase of Glucagon-like peptide-1 in humans in response to cardiac surgery with association to parameters of glucose metabolism

Abstract: ObjectiveGlucagon-like peptide-1 (GLP-1) is an incretin hormone, which gets secreted in response to nutritional stimuli from the gut mediating glucose-dependent insulin secretion. Interestingly, GLP-1 was recently found to be also increased in response to inflammatory stimuli in an interleukin 6 (IL-6) dependent manner in mice. The relevance of this finding to humans is unknown but has been suggested by the presence of high circulating GLP-1 levels in critically ill patients that correlated with markers of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…Kahles et al (42) observed significantly higher levels of GLP-1 in critically ill individuals compared to healthy controls, and speculated on a possible mechanism mediated by interleukin-6 (IL-6). Lebherz et al (43) confirmed this finding, and observed that higher levels of GLP-1 among critically ill individuals were significantly correlated with IL-6 levels. Evidently, since these authors analyzed cohorts of individuals with acute high-grade inflammation, this phenomenon is not comparable to the inflammatory state associated with obesity and T2D.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Kahles et al (42) observed significantly higher levels of GLP-1 in critically ill individuals compared to healthy controls, and speculated on a possible mechanism mediated by interleukin-6 (IL-6). Lebherz et al (43) confirmed this finding, and observed that higher levels of GLP-1 among critically ill individuals were significantly correlated with IL-6 levels. Evidently, since these authors analyzed cohorts of individuals with acute high-grade inflammation, this phenomenon is not comparable to the inflammatory state associated with obesity and T2D.…”
Section: Discussionmentioning
confidence: 76%
“…In regard to the relationship between chronic inflammation and GLP-1, the evidence available to date tends to support that GLP-1 increases in response to inflammation (41)(42)(43)(44) . A pioneering study by Ellingsgaard et al (41) revealed that the administration of interleukin 6 (IL-6) or elevated IL-6 concentrations in response to exercise stimulates GLP-1 secretion from intestinal L-cells and pancreatic alpha cells, improving insulin secretion and blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory Signals Regulate GLP-1 Synthesis, Secretion, and Action Circulating levels of intestinal proglucagon-derived peptides (PGDPs), including GLP-1, were increased in rodents with experimental inflammation induced by injection of cytokines or lipopolysaccharide (LPS) (Ellingsgaard et al, 2011;Kahles et al, 2014;Nguyen et al, 2014). Levels of plasma GLP-1 were also markedly elevated $6.9-fold in 155 critically ill human subjects assessed on admission to an intensive care unit (Kahles et al, 2014), and a smaller but significant 2-fold increase in circulating total GLP-1 levels was observed in 22 non-diabetic human subjects studied within 24 hr of cardiac surgery and cardiopulmonary bypass (Lebherz et al, 2016). In both clinical studies, levels of interleukin-6 (IL-6) were elevated and correlated with plasma levels of total GLP-1.…”
Section: Glp-1: a Target And Mediator Of The Inflammatory Responsementioning
confidence: 90%
“…Interestingly, recent studies have discovered that inflammatory stimuli such as endotoxin and IL-1β stimulate GLP-1 secretion in an IL-6-dependent manner in both mice and human (Kahles, et al 2014; Lebherz, et al 2016; Nguyen, et al 2014). In addition, glucose-dependent insulintropic peptide (GIP) appears to stimulate GLP-1 production in pancreatic islets via induction of IL-6 (Timper, et al 2016).…”
Section: Factors Regulating Intra-islet Glp-1 Productionmentioning
confidence: 99%